KONTRADIKSI IDENTITAS PADA AKOMODASI KOMUNIKASI BUDAYA DALAM IKLAN MARJAN VERSI BELA DIRI 2011 - Yesica Yuliani Clara; Laurencia Steffanie Mega Wijaya Kurniawati (ADISAM PUBLISHER, 2024)
Cultural differences are not always acceptable in society, there is a dominant culture that makes other cultures feel alienated. The lack of people's ability to understand cultural diversity raises issues of intercultural communication, one of the issue is stereotypes about cultures of one another also etnosentrism. In cultural differences, it requires people to adapting new cultures, which is appears in the Marjan Syrup Advertisements on the month of Ramadan in 2011 Martial Art Version entitled